1978
DOI: 10.1111/j.1471-0528.1978.tb14900.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Pregnancy in a 44‐year‐old Haemodialysis Patient

Abstract: A 44-year-old patient had been treated by intermittent haemodialysis for almost three years when she presented with a 28-week pregnancy. Successful delivery of a healthy but small infant was achieved by Caesarean section at 36 weeks. The successful outcome of this pregnancy was attributed to close control of the haemoglobin concentration and blood chemistry, and to increased frequency of dialysis. The relative value of various chemical tests of fetal maturity in the presence of maternal renal failure are discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 9 publications
(11 reference statements)
1
5
0
Order By: Relevance
“…HPL concentrations are significantly higher than nor mal ranges. This is in agreement with Kobayashi et al [2], However, Sheriff et al [11] reported normal HPL level to be associated with pregnancy in patients with renal failure. This peptide has a very short half-life (10-20 min) and is poorly excreted in maternal urine (0.5 mg per day against a production rate of 1 g per day) [13].…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…HPL concentrations are significantly higher than nor mal ranges. This is in agreement with Kobayashi et al [2], However, Sheriff et al [11] reported normal HPL level to be associated with pregnancy in patients with renal failure. This peptide has a very short half-life (10-20 min) and is poorly excreted in maternal urine (0.5 mg per day against a production rate of 1 g per day) [13].…”
Section: Resultssupporting
confidence: 82%
“…Moreover, previous data about E3 concentration during pregnancy associated with renal impairment are controversial. There is a correlation between the renal clearance of E3 and creatinine [5] but in two pregnant women undergoing hemodialysis, E3 was found to be normal [2] or slightly elevated [6,11]. The low level of Et may be related to a deficiency of its substrate.…”
Section: Resultsmentioning
confidence: 97%
“…However, menstrual irregularity and longstanding amenorrhea make the diagnosis of pregnancy difficult. In women with chronic renal failure, most pregnancies are not diagnosed until miscarriage or until the second (46,47,48) (12 through 23 weeks) or even the third (224 weeks) trimester (49). Often the diagnosis is made while investigating symptoms such as worsening nausea, abdominal pain, and fatigue, which overlap with symptoms of uremia (46).…”
Section: The Diagnosis Of Pregnancymentioning
confidence: 99%
“…Most women who are on chronic dialysis or who have chronic renal disease at the time of conception deliver before term. The duration of pregnancy averaged 32.5 weeks in the 21 women who conceived on dialysis for whom data are available (5,8,13,16,18,23,24,25,27,28,29,30,31,52,53). In 21 women who were not on dialysis at the time of conception but required dialysis before the end of pregnancy, the average duration of pregnancy was 34weeks (7,9,11,12,14,15,17,19,21,22,56).…”
Section: Prematuritymentioning
confidence: 99%
“…Most babies born to women with severe chronic renal failure are small for gestational age (4, 5,6,8,13,16,18,23,25,26,28,29,30,45,46,47). The average weight of 22 babies born alive to women who conceived on dialysis was 1422 grams, while that of 22 babies born to women with chronic renal failure not yet on dialysis at the time of conception (but initiating dialysis during pregnancy) was 173 1 grams (1, 2, 9-12, 14-17, 19, 21-23, 27, 31, 56).…”
Section: Growth Retardationmentioning
confidence: 99%